Suicide Behavior in Persons with Intellectual Disability - Joav Merrick; Efrat Merrick; Yona Lunsky; Isack Kandel (The Scientific World Journal)
Suicide is today in the Western world one of the leading causes of death and most people have had suicidal ideation at some time during their life. In the population of persons with intellectual disability some researchers have thought that impaired intellectual capacity could act as a buffer to suicidal behavior, but the fact is that the few studies conducted in that population contest this assumption and showed that the characteristics of suicidality in this population are very similar to persons without intellectual disability. This paper reviews the studies conducted and describe the symptomatology in this population. Professionals working with this population should therefore be aware of and assess for this behavior. Sadness or depression are symptoms that could indicate later suicidal behavior.